Applications of Biotechnology for Characterization of Plants and Pests as the Key Components of Plant Protection and Production Strategies: A Review - Alemu, Melaku (International Journal of Applied Sciences and Biotechnology, 2020)
The second Sustainable Developmental Goals (SDG), among the seventeen SDG, is concerned with the pursuit of global food security and agricultural sustainability, which become the key to the success of the entire SDG. Whereas agricultural production and productivity are heavily threatened by the incidence of pests that inflict huge losses in various forms. This calls for prompt applications of biotechnology for the fast, accurate and reliable means for characterization of plant generic resources and pests as it is the pre-requisite and gateway for designing appropriate plant protection and production strategies. It is imperative that pests be identified properly so that judicious use of the literature can be made and sustainable management strategies can be implemented at the right stage. To this end, the application of biotechnology has made significant advances for reliable characterization of plant genetic resources as well as accurate diagnosis of pests, study of their genetic diversity and variability, detailed mechanisms of their transmission and evolutionary relationships. Accordingly, this review article covers the comprehensive account of the various molecular techniques, genome mapping and OMICS sciences utilized for characterization plants and pests that ultimately allow the detailed study of the biology and epidemiology of pests at any stage of their life cycle. The resulting data are eventually employed for enhancing successful implementation of sustainable plant protection and production strategies. In conclusion, the increasing projections of transboundary pests, environmental and abiotic factors together with the continuous scientific advancements and breakthroughs have made biotechnology to be an important engine of bioeconomy for generating invaluable products, processes and services.Int. J. Appl. Sci. Biotechnol. Vol 8(3): 247-288